Distributional consequences of upstream tree plantations on downstream water users in a Public–Private Benefit Framework. (October 2015) - Nordblom, T.L.; Hume, I.H.; Finlayson, J.D.; Pannell, D.J.; Holland, J.E.; McClintock, A.J.
Abstract: We apply a Public–Private Benefit Framework (PPBF) for new perspectives on the distributional consequences of land-use change in upstream watersheds (wide expansion of tree plantations) negatively affecting downstream water users. Our study area is the Macquarie River catchment in central-west New South Wales, as part of Australia's Murray–Darling Basin, where active water entitlement markets exist downstream. We consider benefits and costs to private upstream landholders allowed to establish new plantations without regard to reduced water flows and qualities to downstream users (urban, agricultural and environmental). Second, we explore a policy requiring new plantations to purchase permanent entitlements in advance for amounts of water they will divert from downstream uses; the calculated increase in evapotranspiration above that of current land-use. With no requirement to purchase entitlements, new plantation areas and their increased water consumption would be greatest, as would negative impacts on downstream water users. Some downstream water users are assumed willing to surrender entitlements at lower prices than others, resulting in an upward-sloping supply curve. Demand for entitlements by new upstream plantations will be functions of anticipated tree product yields, prices, establishment and opportunity costs. Their aggregate demand is downward sloping and intersects the supply curve to define the equilibrium quantity and price of water entitlements traded. With a tree product price of 70/m 3 the economic consequences of unrestricted expansion of planting in the upper watersheds could be in the order of 639M (tree-NPV, 7%) in upstream private net benefit gains, but 388M in uncompensated losses to downstream public net benefits, counting losses of 154 GL in environmental flows valued at 1M/GL, for total catchment net benefits of 251M. The policy as confirmed by our PPBF, indicates "flexible negative incentives" to reduce the expansion of new private plantations by compensating downstream public losses through sale of water entitlements from the latter to the former. Assuming that environmental flows are protected and purchase of downstream water entitlements is required from irrigators and stock and domestic users for new tree plantations, net private benefits of 192M to new plantations are added to 138M in downstream public benefits, improving the net change in catchment benefits to 330M. The policy would improve total net catchment benefit from 251M to 330M, achieving an economically efficient, socially equitable and environmentally sustainable solution, which adjusts automatically over time through the market. Highlights: Upstream tree plantations have greater evapotranspiration than any crop or pasture. Competing downstream water uses include urban, irrigation industry and wetlands. Public–Private Benefit Framework is used to explore distributional consequences. Policy considered for new plantations to purchase downstream water entitlements. Flexible negative incentives appear efficient, equitable & environmentally sound.